Neoadjuvant chemotherapy in local‐regionally advanced nasopharyngeal carcinoma: A National Cancer Database analysis. (22nd August 2018) - Tam, Moses; Lee, Anna; Wu, S. Peter; Gerber, Naamit K.; Li, Zujun; Givi, Babak; Hu, Kenneth; Schreiber, David
Abstract : Objectives/Hypothesis: To assess patterns of care and outcomes with the use of neoadjuvant chemotherapy followed by definitive radiation in local‐regionally advanced nasopharyngeal carcinoma. Study Design: Retrospective database analysis. Methods: We queried the National Cancer Database for patients with T3–4N2 or T1–4N3 nasopharyngeal carcinoma who received concurrent chemoradiotherapy or neoadjuvant chemotherapy followed by radiation. Overall survival (OS) was analyzed using the Kaplan‐Meier method, propensity‐score matching, and a Cox proportional hazards model adjusting for demographic and disease‐specific prognostic factors. Results: From 2004 to 2014, a total of 1, 731 patients were identified, including 504 patients (27%) who received neoadjuvant chemotherapy. Neoadjuvant chemotherapy was used more frequently in years 2008 to 2010 (34%) and 2011 to 2014 (30%) compared with 2004 to 2007 (22%) (χ 2 P  = .001). At a median follow‐up of 36.6 months, patients had 3‐year OS of 66% in the neoadjuvant group compared with 70% in those who received concurrent chemoradiotherapy (log rank P  = .29). On subgroup analysis by histology, T stage, and N stage, there remained no differences in OS between the two groups. On multivariable analysis, there was no significant survival difference associated with neoadjuvant chemotherapy (adjusted hazard ratio [HR]: 1.05, 95% confidence interval [CI]: 0.89‐1.25, P  = .54). In a propensity score–matched population of 1, 008 patients (504 with neoadjuvant therapy and 504 without), there was no significant survival difference associated with neoadjuvant chemotherapy (H: 1.13, 95% CI: 0.93‐1.38, P  = .22). Conclusions: Neoadjuvant chemotherapy was used in over 25% of patients, and its use is increasing. However, neoadjuvant chemotherapy was not associated with any differences in survival compared to concurrent chemoradiotherapy. Level of Evidence: 4 Laryngoscope, 128:2770–2777, 2018